Fundamentals of geomorphology [electronic resource] - Huggett, Richard J. (London ;New York : Routledge, 2007)
This extensively revised and updated second edition of Fundamentals of Geomorphology presents an engaging and comprehensive introduction to geomorphology, exploring the world's landforms from a broad systems perspective. It reflects the latest developments in the field and includes new chapters on geomorphic materials and processes, hillslopes and changing landscapes.
Description based on print version record
Includes bibliographical references (p. [419]-447) and index
Keywords: Geomorphology